MEDIA PEMBELAJARAN DIGITAL MATA PELAJARAN SEJARAH KEBUDAYAAN ISLAM DI SMP IT PLUS AL-BURUJ NW SIKUR BERBASIS ANDROID - Fitriani Fitriani; Hannatul Ma'we; Windrawan Robipul Hakim; Marham Jupri Hadi; Devi Chrisman Lase (Badan Penelitian dan Pengabdian Masyarakat (BP2M) STMIK Syaikh Zainuddin NW Anjani, 2025)
Instructions The development of digital technology has brought major changes in the world of education, including in the method of delivering learning materials. The subject of Islamic Cultural History (ISHC) at SMP IT Plus Al-Buruj NW Sikur still faces the challenge of low student learning interest due to conventional methods that are less interactive. This study aims to design and build Android-based digital learning media to increase the effectiveness and attractiveness of ISHC learning. The application developed includes features of learning materials, videos, practice questions and user profiles, using the Java programming language and SQLite database through the Android Studio platform. The methods used in this study include literature studies, observations and interviews. In addition, system modeling is carried out using the Unified Modeling Language (UML) approach through Use Case, Activity and Class Diagram diagrams. The test results show that this application can support ISHC learning in a more flexible, interactive, and interesting way, both for use in and outside the classroom. This application is expected to be an effective digital solution.